LKB1 exonic and whole gene deletions are a common cause of Peutz-Jeghers syndrome. Issue 5 (28th April 2006) - Volikos, E; Robinson, J; Aittomäki, K; Mecklin, J-P; Järvinen, H; Westerman, A M; de Rooji, F W M; Vogel, T; Moeslein, G; Launonen, V; Tomlinson, I P M; Silver, A R J; et al.
Abstract : Background: LKB1/STK11 germline mutations cause Peutz-Jeghers syndrome (PJS). The existence of a second PJS locus is controversial, the evidence in its favour being families unlinked to LKB1 and the low frequency of LKB1 mutations found using conventional methods in several studies. Exonic and whole gene deletion or duplication events cannot be detected by routine mutation screening methods. Objective: To seek evidence for LKB1 germline deletions or duplications by screening patients meeting clinical criteria for PJS but without detected mutations on conventional screening. Methods: From an original cohort of 76 patients, 48 were found to have a germline mutation by direct sequencing; the remaining 28 were examined using multiplex ligation dependent probe amplification (MLPA) analysis to detect LKB1 copy number changes. Results: Deletions were found in 11 of the 28 patients (39%)—that is, 14% of all PJS patients (11/76). Five patients had whole gene deletions, two had the promoter and exon 1 deleted, and in one patient exon 8 was deleted. Other deletions events involved: loss of exons 2–10; deletion of the promoter and exons 1–3; and loss of part of the promoter. No duplications were detected. Nine samples with deletions were sequenced at reported single nucleotide polymorphisms to exclude heterozygosity; homozygosity was found in all cases. No MLPA copy number changes were detected in 22 healthy individuals. Conclusions: These results lessen the possibility of a second PJS locus, as the detection rate of germline mutations in PJS patients was about 80% (59/76). It is suggested that MLPA, or a suitable alternative, should be used for routine genetic testing of PJS patients in clinical practice.